An econometric model of the world cobalt industry - M. Reza Rafati (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1982)
One of the main still unresolved issues discussed at the United Nations Conference on the Law of the Sea has been the potential impact of the recovery of cobalt, copper, manganese and nickel from seabed nodules on the markets of those metals. It has been argued that the start of seabed mining could significantly affect both prices and production if a free entry regime prevailed. In order to provide a sound empirical basis for further discussions of this topic the present study aims at quantifying the potential effects of seabed mining on the cobalt market. First, an econometric model of the world cobalt industry is specified and estimated. Next, the model is simulated for different scenarios: no exogenous change, the start of the stockpiling of cobalt by the US government, and the start of seabed mining. The study concludes that the reduction in cobalt prices, as a result of seabed mining, will be drastic, particularly in the free entry case, and that the major revenue loser will be Zaire, the world's largest producer of cobalt.
Keywords: 330